Resilience in Bali's Accommodation Businesses Amidst COVID-19 Pandemic: A Survival Analysis - Ni Made Inna Dariwardani; I Wayan Suardana; I Nyoman Sunarta; I Gusti Putu Bagus Sasrawan Mananda; Ignatius Cahyanto (Pusat Kajian Bali Universitas Udayana, 2025)
This study aims to estimate the survival rate of the accommodation industry in Bali during the COVID-19 pandemic crisis using a dataset comprising 3,378 accommodations in Bali. Two distinct survival analysis methodologies were employed: the Kaplan-Meier and log-rank tests. This study will also employ a qualitative analysis to examine the cultural characteristics of accommodation business resilience in Bali. Based on the patterns revealed in this research, hotels in operation for the last 10 years will have a 70% survival rate, in contrast with hotels in operation for over 40 years which have a 25% survival rate. This is especially the case of hotels that remain in operation during the COVID-19 pandemic. The initial 15-year period of business operations is identified as a critical juncture. Moreover, a notable discrepancies in survival rates was found across groups defined by specific variables, including the number of rooms, business scale, business typology, and location. Local culture is also discovered to be a crucial factor that enhances business adaptability and community ties, providing resilience.